Structure and Agency in Discourse Analysis - Girkontaitė, Agnė (Sociologija. Mintis ir veiksmas, 2018)
[full article and abstract in Lithuanian; abstract in English]Discourse analysis in Lithuania, despite being a popular research strategy, lacks clarity and precision in methodological choices. It is quite common to use Foucault’s approach while discussing discourse, but it leads to an overemphasis on structure and ignores agency. However, there is no issue if this position is reflected. That is why it is important to understand the variety of the possible positions in the dialectics of structure-agency within discourse analysis. They are summarized here within a continuum that rests between an emphasis on structure and an emphasis on agency, and which is divided as follows: (1) being concerned exclusively with the structure of discourse without any attention to the agent; (2) being concerned with discourse structure as something that lies “beyond,” where agents are more or less seen as the passive carriers of a discursive order with almost no possibility of agency; (3) the discourse and agent being seen as taking part in a balanced dialectical relationship, influencing each other; (4) the agent being seen as dependent on structure to some extent, but also as the one with the power or the one who should be empowered; (5) the center of an analysis being the practices of the actors, not the discourse in particular. This classification explains the specific epistemological and methodological strategies based in specific areas of the social sciences and the humanities. When reflected, these strategies help to understand what position on the role of agency is taken in a particular discourse analysis.
Keywords: discourse analysis, agency, structure, social science methodology, reflection